Photoprotective Non-photochemical Quenching Does Not Prevent Kleptoplasts From Net Photoinactivation - Christa, Gregor; Pütz, Laura; Sickinger, Corinna; Melo Clavijo, Jenny; Laetz, Elise M. J.; Greve, Carola; Serôdio, João (Frontiers in Ecology and Evolution, 2018)
The enigmatic association of photosynthetically active chloroplasts from algae and some sacoglossan sea slugs, called functional kleptoplasty, is a functional unique system of photosymbioses observed in metazoans. Besides the specific adaptations of the slugs necessary to incorporate and maintain the plastids, the organelles need to ensure optimal photosynthesis. Photoprotective mechanisms in the plastids, namely the xanthophyll cycle (XC) and the high-energy dependent quenching (qE) part of the non-photochemical quenching (NPQ), and of the repair of the D1 protein of Photosystem II (PSII) are considered crucial for kleptoplast longevity in the slugs. Here, we studied the sea slugs Elysia viridis fed with the naturally occurring XC and qE-deficient Bryopsis hypnoides, and E. timida fed on Acetabularia acetabulum, an alga that possesses both mechanisms. The aim of the study was to understand (i) whether qE remains active after ingestion of kleptoplasts by E. timida, (ii) how different light intensities affect the photosynthetic activity of kleptoplasts with and without photoprotection mechanisms, and (iii) if the kleptoplasts are able to repair photodamaged D1 protein. With regard to NPQ, freshly incorporated kleptoplasts responded to different light stress in the same manner as the chloroplasts in their native host algae. Even after three weeks of incorporation the qE part of NPQ was present in the kleptoplasts of E. timida. However, the presence of the qE component of NPQ did not prevent the kleptoplasts from significant PSII photoinactivation under high light intensities. This is probably due to the fact that the kleptoplasts have a reduced PSII repair capacity, despite plastid encoded repair mechanisms in every sacoglossan food source. Hence, photoprotective mechanisms are probably not a key factor explaining kleptoplast longevity in Sacoglossa sea slugs.